The manipulation of fructose 2,6-bisphosphate levels in sugarcane - Hiten, Nicholas Fletcher (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Plant Biotechnology))--University of Stellenbosch, 2006.